How a new clothing brand like Twelve clothing penetrated the RMG industry of Bangladesh - Ashhab, Md. Rakin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.